Improvement of Knowledge and Attitudes on Tuberculosis Patients with Poster Calendar and Leaflet - Siregar, Putra Apriadi; Ashar, Yulia Khairina; Hasibuan, Reni Ria Armayani; Nasution, Fauziah; Hayati, Fitri; Susanti, Nofi (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Background: Leaflet and poster calendars are one medium to provide health education to patients with pulmonary tuberculosis on the treatment of pulmonary Tuberculosis. The purpose of this research for media want to effectivity leaflet and poster calendars on health promotion to improve the knowledge and attitudes of pulmonary tuberculosis treatment at the Martubung Public Health Center. Methods: Research is a quasi-experimental design with pre-test and post-test group. The population in this study were all patients with pulmonary tuberculosis treatment in Martubung Public Health Center and analyzed with the wilcoxon test. Results: The results of the study using the wilcoxon test showed that the leaflet could increase the pretest value of 10 knowledge to 11.03 (p <0.001) and the attitude of having a pretest value of 41.77 to 45.7 (p <0.001). The wilcoxon test results show that the poster calendar can increase the pretest knowledge value from 8.7 to 11.97 (p <0.001) and the pretest attitude value from 43.7 to 50.27 (p <0.001). Conclusions: The media are most effective in improving knowledge and attitudes about the treatment of patients with pulmonary tuberculosis disease in Martubung Public Health Center is media poster calendar from the average value based on the pre-test and post-test conducted.